Coffee, Black Tea, and Green Tea Consumption in Relation to Plasma Metabolites in an Asian Population. Issue 24 (16th November 2020) - Seow, Wei Jie; Low, Dorrain Yanwen; Pan, Wen‐Chi; Gunther, Samuel H.; Sim, Xueling; Torta, Federico; Herr, Deron R.; Kovalik, Jean‐Paul; Ching, Jianhong; Khoo, Chin Meng; Wenk, Markus R.; Tai, E Shyong; et al.
Abstract : Scope: Coffee and tea are among the most popular beverages in the world. However, the association between habitual coffee, green tea, and black tea consumption with metabolomics profiles in Asian populations remain largely unknown. Methods and Results: 158 metabolites (14 amino acids, 45 acylcarnitines, and 99 sphingolipids) in the blood plasma of participants are measured from the population‐based Singapore Prospective Study Program cohort using mass spectrometry (MS). Linear regression models are used to obtain the estimates for the association between coffee and tea consumption with metabolite levels, adjusted for potential confounders and false discovery rate (FDR). Coffee consumption is significantly associated with higher levels of 63 sphingolipids (29 sphingomyelins, 32 ceramides, a sphingosine‐1‐phosphate, and a sphingosine) and lower levels of 13 acylcarnitines and alanine. Black tea consumption is significantly associated with higher levels of eight sphingolipids, and lower levels of an amino acid, whereas green tea is significantly inversely associated with four metabolites (C8:1‐OH acylcarnitine, ganglioside GM3 d18:1/16:0, sphingomyelins d18:2/18:0 and d18:1/14:0). Conclusions: Coffee, black tea, and green tea consumption are associated with plasma levels of certain classes of sphingolipids and acylcarnitines in an Asian population, particularly sphingomyelins, which may mediate the health benefits of these beverages. Abstract : Coffee, black tea, and green tea consumption are associated with plasma levels of certain classes of sphingolipids and acylcarnitines in an Asian population, which may mediate the health benefits of these beverages.